55. COMPLIANCE WITH ARV TREATMENT IN HIV/AIDS INFECTED PEOPLE AT BEN LUC DISTRICT MEDICAL CENTER, LONG AN PROVINCE IN 2025 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Problem statement: Adherence to ARV treatment is an important factor in controlling HIV/AIDS and reducing the risk of drug resistance, however, the local adherence rate is still low compared to WHO recommendations.Objective: Describe the current status of adherence to ARV treatment and related factors in people with HIV/AIDS receiving outpatient treatment at Ben Luc District Medical Center, Long An in 2024.Method: Cross-sectional study describing 220 people with HIV/AIDS receiving outpatient ARV treatment, randomly selected sample, data collection by direct interview, analyzed by SPSS.Results: The overall adherence rate to ARV treatment was 75%, follow-up visits on time 75.9%, testing on time 72.3%, taking the right dose 77.7%. Related factors include age ≥35, stable employment, no side effects, regular medical information lookup, no co-infections, and good knowledge of HIV/AIDS.Conclusion: The rate of ARV treatment adherence is relatively good but does not reach the WHO recommended level; related factors are identified to support the development of local adherence-enhancing interventions.
Keywords: ARV treatment adherence; HIV/AIDS; Ben Luc; Long An.